1987
DOI: 10.1016/0011-5029(87)90022-8
|View full text |Cite
|
Sign up to set email alerts
|

Dermatomyositis

Abstract: Dermatomyositis and polymyositis are related disorders of unknown cause in which immunologic changes may be important. They sometimes overlap with other collagen vascular diseases, and not infrequently are associated with malignancy. The clinical features of the adult and juvenile forms of the disorder and the visceral manifestations of DM-PM are outlined, along with enzymatic, electromyographic, and histologic aids to diagnosis. While the cutaneous lesions often are resistant to treatment, systemic involvemen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

1992
1992
2010
2010

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 16 publications
(2 citation statements)
references
References 194 publications
0
2
0
Order By: Relevance
“…This opens the possibility that juvenile DMS may be a syndrome with many variations. Callen (17) reported that skin lesions from DMS can be difficult to treat and may stay the same or even worsen even when symptoms otherwise abate through treatment. The fact that intractable cutaneous manifestations were seen in our cases ofjuvenile DMS as well makes us wonder whether some factor unique to juvenile DMS could be involved which would make it an entity separate from adult DMS.…”
Section: Discussionmentioning
confidence: 99%
“…This opens the possibility that juvenile DMS may be a syndrome with many variations. Callen (17) reported that skin lesions from DMS can be difficult to treat and may stay the same or even worsen even when symptoms otherwise abate through treatment. The fact that intractable cutaneous manifestations were seen in our cases ofjuvenile DMS as well makes us wonder whether some factor unique to juvenile DMS could be involved which would make it an entity separate from adult DMS.…”
Section: Discussionmentioning
confidence: 99%
“…2 Polymyositis is differentiated from dermatomyositis by the absence of the characteristic cutaneous lesions. 1 Stahl et al 3 reported the presence of hyperkeratosis of the fleshy pad and the lateral aspect of the fingers to be a marker for idiopathic inflammatory myositis. We describe a woman with primary polymyositis associated with hyperkeratosis of the fingers of both hands.…”
mentioning
confidence: 99%